The level of application by cow breeders of scientific recommendations related to hemorrhagic fever disease in the Gogjali region - Mahal, Mohammed Ahmed (Journal of agricultural, environmental and veterinary sciences, 2025)
The aim of this study is to determine the level of application of cattle breeders who live in the Gogjali region during the period 2023-2024 , east of Nineveh Governorate, for the scientific recommendations related to hemorrhagic fever disease, in addition to identifying the correlation between personal factors and the dependent factor, as well as identifying the obstacles facing the control of this disease, the research sample consisted of 170 respondents representing 50% of the research community, the research tool consisted of three parts. The first part included 5 independent variables, the second part consisted of 23 items related to measures derived from scientific recommendations, while the third part consisted of 8 paragraphs measuring the obstacles that limit the control of the disease. The tool was presented in its initial form to some specialists to verify the content validity, and then the value of the Cronbach alpha coefficient was found , it is a statistical tool used to make sure that if the questionnaire is distributed a second time , the results will be the same as the first time , and its value in this study which was 0.88. The results showed that 82% of breeders had average application level and tended to decrease. The results showed a significant correlation between the dependent variable and the following variables (age, educational level, size of the breeder’s possession of cows, level of exposure of the breeder to sources of information about the disease). conclusion shows that the study area is threatened by a widespread outbreak of the disease due to the respondents’ weak application of scientific recommendations. due to the respondents’ weak application of scientific recommendations.